2011
DOI: 10.3389/fnana.2011.00057
|View full text |Cite
|
Sign up to set email alerts
|

Combined Liquid and Solid-Phase Extraction Improves Quantification of Brain Estrogen Content

Abstract: Accuracy in quantifying brain-derived steroid hormones ("neurosteroids") has become increasingly important for understanding the modulation of neuronal activity, development, and physiology. Relative to other neuroactive compounds and classical neurotransmitters, steroids pose particular challenges with regard to isolation and analysis, owing to their lipid solubility. Consequently, anatomical studies of the distribution of neurosteroids have relied primarily on the expression of neurosteroid synthesis enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…These studies are ongoing in our laboratory. Using the same extraction and analysis techniques utilised in our experiment, Chao et al (32) measured approximately 10 pg/mg of E 2 in the posterior and anterior portions of the telencephalon of uninjured male zebra finches. Although this concentration is higher than our measurements for the male uninjured telencephalon of the brain, it is decreased compared to our concentrations from the male injured telencephalon (approximately 19 pg/mg).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These studies are ongoing in our laboratory. Using the same extraction and analysis techniques utilised in our experiment, Chao et al (32) measured approximately 10 pg/mg of E 2 in the posterior and anterior portions of the telencephalon of uninjured male zebra finches. Although this concentration is higher than our measurements for the male uninjured telencephalon of the brain, it is decreased compared to our concentrations from the male injured telencephalon (approximately 19 pg/mg).…”
Section: Discussionmentioning
confidence: 98%
“…As described previously (32,33), E 2 is readily detectable in the zebra finch brain. Statistical analyses using log-transformed data revealed that levels of E 2 were significantly increased in injured brain tissue compared to uninjured brain tissue (Figs 2 and 3) of adult male (t 4 = À2.46, P = 0.035) and female (t 4 = 2.99, P = 0.02) zebra finches 48 h after injury.…”
Section: Experiments 2: Oestradiol Enzyme Immunoassaymentioning
confidence: 96%
See 3 more Smart Citations